Preparing Engineering Students for the Global Sourcing Environment - Manzione, Louis; Abuaisheh, Akram; Sumukadas, Narendar; Congden, Steve (International Journal of Advanced Corporate Learning (iJAC), 2017)
Abstract—Globalization and rapid changes in modern product development and realization are creating gaps in engineering education systems around the world. The global economy has changed the way that engineering firms design, develop, and produce their products. Companies need to evaluate many options available worldwide, not just locally. The current trends are only likely to continue as the world economy becomes more competitive, interdependent, and characterized by global relationships among supply chain partners. This paper presents a plan for preparing engineering students for the new global sourcing environments and product realization processes. Infusions of supply chain management and project management skills into the curriculum are recommended, as well as use of university-industry partnerships, course portfolios, and study abroad programs.